Compact Groups analysis using weak gravitational lensing II: CFHT Stripe 82 data - Chalela Garcia, Martin (2018)
In this work we present a lensing study of Compact Groups (CGs) using data obtained from the high-quality Canada-France-Hawaii Telescope Stripe 82 Survey. Using stacking techniques we obtain the average density contrast profile. We analyse the lensing signal dependence on the groups' surface brightness and morphological content, for CGs in the redshift range z = 0.2-0.4.We obtain a larger lensing signal for CGs with higher surface brightness, probably due to their lower contamination by interlopers. Also, we find a strong dependence of the lensing signal on the group concentration parameter, with the most concentrated quintile showing a significant lensing signal, consistent with an isothermal sphere with σV = 336 ± 28 km s-1 and a NFW profile with R200 = 0.60 ± 0.05 h-1 70 Mpc. We also compare lensing results with dynamical estimates finding a good agreement with lensing determinations for CGs with higher surface brightness and higher concentration indexes. On the other hand, CGs that are more contaminated by interlopers show larger dynamical dispersions, since interlopers bias dynamical estimates to larger values, although the lensing signal is weakened.